2021
DOI: 10.1192/j.eurpsy.2021.1758
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and suicidal ideation during the COVID-19 pandemic in Russia

Abstract: IntroductionThe COVID-19 pandemic may bear serious consequences for mental health, such as the increase in psychopathological symptoms.ObjectivesAnalysis of changes in depressive suicidal ideation symptoms and during the COVID-19. Depressive symptoms and suicidality were considered separately.MethodsInternet survey 22.03.20–22.06.20 (908 responses), included SCL-90R, COPE, question about suicidal ideation.ResultsThe analysis showed a positive correlation between suicidal thoughts and depression (Spearman .45; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Indications for the transfer were persistent suicidal tendencies, low mood, lack of plans for the future, as well as the lack of prospects (from Patients with personality/behavior disorders more often than others pointed to the connection between psychological well-being and COVID-19, and the reasons for their problems were the changes resulting from a lockdown in the healthcare system [3]. According to domestic data, the growth of depressive symptoms is due to various fears and is mediated by non-constructive ways of coping with stress [13]. Data on the increase in the sale of antidepressants and tranquilizers in Russia for the Symptoms of anxiety during the pandemic were often observed in the framework of adaptation disorders, generalized anxiety disorders, somatoform disorders, including panic attacks [11].…”
Section: Related: "Coronavirus Infection Covid-19 Virus Identified"mentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for the transfer were persistent suicidal tendencies, low mood, lack of plans for the future, as well as the lack of prospects (from Patients with personality/behavior disorders more often than others pointed to the connection between psychological well-being and COVID-19, and the reasons for their problems were the changes resulting from a lockdown in the healthcare system [3]. According to domestic data, the growth of depressive symptoms is due to various fears and is mediated by non-constructive ways of coping with stress [13]. Data on the increase in the sale of antidepressants and tranquilizers in Russia for the Symptoms of anxiety during the pandemic were often observed in the framework of adaptation disorders, generalized anxiety disorders, somatoform disorders, including panic attacks [11].…”
Section: Related: "Coronavirus Infection Covid-19 Virus Identified"mentioning
confidence: 99%
“…Suicidal mood is associated with a high level of stress, and for the development of thoughts about suicide, it is not necessary to have a real threat, it is enough to have the fear of the possibility of infection, or the fear of dying from an incurable disease or losing your relatives for this same reason [13]. Many authors, both in our country and abroad, have pointed to an increase in suicidal mood in general [17].…”
Section: Related: "Coronavirus Infection Covid-19 Virus Identified"mentioning
confidence: 99%
“…A study in Mexico showed that the prevalence of suicidal ideation was 2.3%, that 1.5% showed a suicide plan or attempt, and that suicide attempts were more common in urban than in rural areas [19]. Similarly, in Russia, positive and significant correlations between suicidal thinking and depression were found in 908 people [20]. In France, loneliness and boredom were independent predictors of depression, anxiety and insomnia in vulnerable people, whereas daily physical activity was a protective factor; virtual contacts also protected against suicidal ideation [21].…”
Section: Introductionmentioning
confidence: 99%